The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1186/1749-8090-7-95
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes in cardiac surgery in 500 consecutive Jehovah's Witness patients: 21 year Experience

Abstract: BackgroundRefusal of heterogenic blood products can be for religious reasons as in Jehovah's Witnesses or otherwise or as requested by an increasing number of patients. Furthermore blood reserves are under continuous demand with increasing costs. Therefore, transfusion avoidance strategies are desirable. We describe a historic comparison and current results of blood saving protocols in Jehovah's Witnesses patients.MethodsData on 250 Jehovah's Witness patients operated upon between 1991 and 2003 (group A) were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
79
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 67 publications
(82 citation statements)
references
References 19 publications
(22 reference statements)
0
79
0
1
Order By: Relevance
“…Although there are previous reports of management and outcomes for patients who do not accept ABT, [4][5][6][7][8][9][10][11][12][13][14][15][16][17] most are series of cases of surgical patients with simple outcome measures, such as length of stay and mortality, without matched control groups for comparison. [5][6][7][8][9][10][11][12][13][14][15][16][17] A study from 2002 showed that the risk of death in surgical patients with a postoperative hemoglobin level of 7.1-8.0 was low, although a morbid event (defined as a myocardial infarction, arrhythmia, congestive heart failure, or infection) occurred in 9.4% of patients.…”
Section: Previous Studies Of Bloodless Medicinementioning
confidence: 99%
See 4 more Smart Citations
“…Although there are previous reports of management and outcomes for patients who do not accept ABT, [4][5][6][7][8][9][10][11][12][13][14][15][16][17] most are series of cases of surgical patients with simple outcome measures, such as length of stay and mortality, without matched control groups for comparison. [5][6][7][8][9][10][11][12][13][14][15][16][17] A study from 2002 showed that the risk of death in surgical patients with a postoperative hemoglobin level of 7.1-8.0 was low, although a morbid event (defined as a myocardial infarction, arrhythmia, congestive heart failure, or infection) occurred in 9.4% of patients.…”
Section: Previous Studies Of Bloodless Medicinementioning
confidence: 99%
“…[1][2][3] In fact, several academic health centers are establishing "Bloodless Medicine & Surgery Programs" that specialize in treating patients who do not accept allogeneic blood transfusions (ABTs). [4][5][6][7][8][9][10][11][12][13][14][15][16] A multidisciplinary approach is frequently required to optimize clinical outcomes for these patients, particularly in the setting of multiple comorbidities or high-risk surgical procedures.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations